ANALISIS PRODUKSI DAN EFISIENSI INDUSTRI KECIL DAN MENENGAH (IKM) BATIK TULIS DI KOTASEMARANG - Bella Aldida; Purbayu Budi Santosa (Universitas Diponegoro, 2013)
The study was conducted on the small and medium industry batik in Semarang. Respondents are SME entrepreneurs batik with the number of 41 people, the vast majority of their business is still relatively small scale. The research objective is to: (1) describe the general condition of batik in Semarang, (2) analyze the influence of factors of production such as fabrics, wax, dye medicine, labor and fuel for the production of batik, and (3) estimate the efficiency of production, prices and the economy batik small-medium industries in Semarang. The results showed that the variables of fabrics, dyes medicine and labor has a positive and significant impact on the production of batik, while variables wax and fuel has no significant effect. The level of technical efficiency in the research object is said to be efficient with an average rating of less than one (0.87). Analysis of allocative efficiency and economy suggests that the use of production factors is inefficient with values ​​respectively 0.894 and 0.778. To achieve a more efficient outcome it is necessary to increase the input fabrics and dye medicines, a review of the use of wax and reduced fuel when necessary, as well as further guidance to the workforce.